Impact of immune reconstitution inflammatory syndrome on antiretroviral therapy adherence - Nachega JB; Morroni C; Chaisson RE; Goliath R; Efron A; Ram M; Maartens G (Patient Preference and Adherence, 2012)
Jean B Nachega,1,2,4 Chelsea Morroni,1 Richard E Chaisson,2–4 Rene Goliath,1 Anne Efron,4 Malathi Ram,2 Gary Maartens11University of Cape Town, Department of Medicine, Division of Clinical Pharmacology, Cape Town, South Africa; 2Johns Hopkins University, Bloomberg School of Public Health, Departments of International Health and Epidemiology, 3Johns Hopkins University, School of Medicine, Department of Medicine, Division of Infectious Diseases, 4Johns Hopkins University, Center for Tuberculosis Research, Baltimore, Maryland, USAObjective: We determined the impact of immune reconstitution inflammatory syndrome (IRIS) on antiretroviral therapy (ART) adherence in a cohort of 274 human immunodeficiency virus (HIV)-infected South African adults initiating ART.Methods: We carried out a secondary analysis of data from a randomized controlled trial of partially supervised ART in Cape Town, South Africa. Monthly pill count adherence, viral suppression (HIV viral load < 50 c/mL), and IRIS events were documented. Poisson regression was used to identify variables associated with ART adherence below the median in the first 6 months of ART.Results: We enrolled 274 patients: 58% women, median age 34 years, median CD4 count 98 cells/µL, 46% World Health Organization clinical stage IV, and 40% on treatment for tuberculosis (TB). IRIS and TB-IRIS developed in 8.4% and 6.6% of patients, respectively. The median cumulative adherence at 6 months for those with an IRIS event vs no IRIS was 95.5% vs 98.2% (P = 0.04). Although not statistically significant, patients developing IRIS had a lower 6-month viral load suppression than those without IRIS (68% vs 80%, P = 0.32). ART adherence below the median of 98% was independently associated with alcohol abuse (relative risk [RR] 1.5; 95% confidence interval [CI] 1.2–1.9; P = 0.003) and IRIS events (RR 1.7; 95% CI 1.2–2.2; P = 0.001).Conclusion: Although IRIS events were associated with slightly lower adherence rates, overall adherence to ART remained high in this study population. Concerns about IRIS should not deter clinicians from early ART initiation.Keywords: ART, adherence, TB, HIV/AIDS, IRIS